Saúde bucal e educação infantil: avaliação do desgaste e do acondicionamento de escovas dentárias utilizadas por pré-escolares - Garbin, Cléa Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Arcieri, Renato Moreira [UNESP]; Souza, Neila Paula de [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2012)
Introduction: Early childhood is an essential phase of life for the future of oral health. The link between educational and health sectors can facilitate incorporating educational and preventive oral health practices in daily teaching in pre-schools. The main measure is manual tooth-brushing, which is the most accessible method for most of the population. Objective: The objective of this study is to evaluate macroscopically the wear on the bristles, form of storage, and identification of tooth brushes. Material and method: 345 toothbrushes used by children between the ages of 2 and 5 were evaluated in 4 pre-schools, by 2 participants from the oral health program. The Rawls et al. index was used to evaluate the bristles. Result: There were statistically significant differences (p = 0.020 - Mann-Whitney U test) between the frequency of toothbrushes, with the highest being (n = 205) stored at participating school; and, between adequate and inadequate brushes (p < 0.05 - X2 test) with 31.7 and 60%, respectively, classified as unfit for tooth-brushing. Of the toothbrush holders evaluated 100% were used collectively. Regarding identification, 18% of the toothbrushes were not identified in participating schools, and 37% in the others. Conclusion: The toothbrushes exhibited marked wear, and storage was inadequate; however, the schools participating in the oral health program showed toothbrushes with bristles less worn. It is suggested that training of educators regarding correct storage and evaluation of toothbrushes for wear of the bristles should be undertaken in all early childhood schools.

Introdução: A infância é uma fase da vida de importância primordial para o futuro da saúde bucal. O elo entre os setores da educação e da saúde pode oportunizar a incorporação de práticas educativas e preventivas em saúde bucal no cotidiano pré-escolar. A principal medida é a escovação dentária manual – método mais acessível para a maioria da população. Objetivo: Avaliar macroscopicamente o desgaste das cerdas, a forma de acondicionamento e a identificação das escovas dentárias. Material e método: Foram avaliadas 345 escovas utilizadas por crianças de 2 a 5 anos, em quatro escolas de educação infantil, sendo duas participantes do programa de promoção de saúde bucal. Empregou-se o índice de Rawls et al. para avaliar as cerdas. Resultado: Diferenças estatisticamente significantes (p = 0,020 - teste U de Mann-Whitney) foram comprovadas entre as frequências de escovas, sendo a maior (n = 205) verificada em escola participante do programa; e, entre escovas adequadas e inadequadas (p < 0,05 - teste X2 ), em que 31,7 e 60% das escovas das escolas participantes e não participantes do programa, respectivamente, foram classificadas como impróprias para a escovação. Dos porta-escovas avaliados, 100% eram de uso coletivo. Quanto à identificação, 18% das escovas não estavam identificadas nas escolas participantes e 37% nas demais. Conclusão: A maioria das escovas apresentou desgastes acentuados e o acondicionamento das mesmas era inadequado; entretanto, as escolas participantes do programa apresentaram escovas com cerdas menos desgastadas. Sugere-se que haja a capacitação do educador quanto ao correto acondicionamento e à avaliação das escovas em relação ao desgaste das cerdas em todas as escolas de educação infantil.
Oral health and early childhood education: evaluation of the wear and storage of toothbrushes used by preschoolers
Keywords: Toothbrushing; Dental devices; Home care; Oral hygiene; Health education; Child; Preschool; Escovação dentária; Dispositivos para o cuidado bucal domiciliar; Higiene bucal; Educação em saúde; Pré-escolar